Penguatan Literasi Keuangan Dalam Mengelola Keuangan Pribadi Pada Siswa SMK IPTEK Tangerang Selatan - Aat Sutihat; Liasari Fajarwati (Jurnal PKM Manajemen Bisnis, 2026)
The low level of financial literacy among adolescents has become a critical issue that requires serious attention, particularly for vocational high school (SMK) students who are beginning to manage their finances independently. Limited understanding of personal financial management can lead to consumptive behavior, weak saving habits, and increased vulnerability to the misuse of digital financial services. This Community Service Program aimed to enhance the financial literacy of SMK students through applicative and contextual education on personal financial management. The program was implemented at SMK IPTEK and involved 35 students as participants. The PKM activities were conducted by five lecturers from the Undergraduate Accounting Study Program of Universitas Pamulang on September 27, 2025. The implementation methods included interactive counseling sessions, participatory discussions, budgeting simulations, and the introduction of potential digital financial risks. Program evaluation was carried out by comparing students’ knowledge and skills before and after the activities. The results showed a significant improvement in students’ financial understanding and competencies, particularly in distinguishing between needs and wants, preparing simple personal budgets, and increasing awareness of digital financial risks. These findings indicate that structured and participant-oriented financial education is effective in improving financial literacy. This PKM program contributes to fostering responsible financial behavior among SMK students and is expected to serve as a sustainable community service model supported by schools and relevant stakeholders.